Novel photochemical reactions of carbocyclic diazodiketones without elimination of nitrogen – a suitable way to N-hydrazonation of C–H-bonds - Rodina, Liudmila L.; Azarova, Xenia V.; Medvedev, Jury J.; Semenok, Dmitrij V.; Nikolaev, Valerij A. (Beilstein Journal of Organic Chemistry, 2018)
The sensitized photoexcitation of 2-diazocyclopentane-1,3-diones in the presence of THF leads to the insertion of the terminal N-atom of the diazo group into the α-С–Н bond of THF, producing the associated N-alkylhydrazones in yields of up to 63–71%. Further irradiation of hydrazones derived from furan-fused tricyclic diazocyclopentanediones culminates in the cycloelimination of furans to yield 2-N-(alkyl)hydrazone of cyclopentene-1,2,3-trione. By contrast, the direct photolysis of carbocyclic diazodiketones gives only Wolff rearrangement products with up to 90–97% yield.
Keywords: C–H insertion; diazo compounds; excited state; photochemistry; Wolff rearrangement